Application of Role Play Techniques in Efforts to Improve Students' Language Vocabulary - Wardhani, Ade Puspita; Wafda , Andi (Pustaka Digital Indonesia, 2022)
The purpose of this study was to improve the vocabulary skills of grade 3 students at SDN Kincang 02 Jiwan by applying the Role Play Technique. This research is a Classroom Action Research (CAR) with a cycle model that is carried out repeatedly and continuously. The subjects of this study were 19 students in grade 3 and the object was thematic learning for grade 3 students at SDN Kincang 02 Jiwan. Data analysis used descriptive qualitative analysis. The results of the study showed an increase in students' language and communication skills. Students' language and communication abilities can improve student learning outcomes and abilities have an impact on student learning completeness from the average score on the initial student data which is 59.64 and has a learning mastery of 57.14% and at the end of the first cycle the average value of students becomes 67.86 with learning completeness to 71.43% and at the end of the second cycle the average value of students rose to 75 with student completeness reaching 92.2%. Apart from increasing learning outcomes, student activity in the learning process in class has also increased. The conclusion from this research is that the role play technique can have a positive effect on student achievement in thematic learning activities for grade 3 students at SDN Kincang 02. The findings in this study are that students have started to dare to ask questions and respond to questions from the teacher by understanding interviews and writing down a list of questions to conduct interviews